A review of utility of wearable sensor technologies for older person frailty assessment - Chen Yixiao; Shen Hui; Song Quhong; Zeng Xiaoxi; Yue Jirong (Experimental Gerontology)
Frailty is one of the most concerning aspects of global population aging, and early identification is crucial to prevent or reverse its progression. Simple, universal, and efficient frailty assessment technologies are essential for the timely detection of frailty in older patients. Various multi-dimensional assessment instruments have been developed to quantify frailty phenotypes; we review the literature on wearable sensor technologies leveraged for older person frailty assessment. This review examines representative studies on older person frailty assessment published up to 2024, summarizing pertinent wearable sensor technologies utilized for frailty assessment. Our findings suggest that objective, simple, rapid, and affordable sensor-based frailty screening holds utility across diverse applications including diagnostic aid, prognostication, and endpoint ascertainment in research.